2009
DOI: 10.1038/nphys1255
|View full text |Cite
|
Sign up to set email alerts
|

High-fidelity transmission of entanglement over a high-loss free-space channel

Abstract: Quantum entanglement enables tasks not possible in classical physics. Many quantum communication protocols [1] require the distribution of entangled states between distant parties. Here we experimentally demonstrate the successful transmission of an entangled photon pair over a 144 km free-space link. The received entangled states have excellent, noise-limited fidelity, even though they are exposed to extreme attenuation dominated by turbulent atmospheric effects. The total channel loss of 64 dB corresponds to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
180
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 191 publications
(182 citation statements)
references
References 25 publications
(58 reference statements)
2
180
0
Order By: Relevance
“…(13) is plotted as a function of α and q setting ν 2 = 0.4 π for the initial state (22). We note that it exhibits a sudden change across the q ≈ 0.54 line.…”
Section: Fig 9 (Color Online)mentioning
confidence: 99%
See 1 more Smart Citation
“…(13) is plotted as a function of α and q setting ν 2 = 0.4 π for the initial state (22). We note that it exhibits a sudden change across the q ≈ 0.54 line.…”
Section: Fig 9 (Color Online)mentioning
confidence: 99%
“…[17] for a recent review). This is not only interesting in its own right but may also have practical importance because of new trends of implementing quantum-information protocols at global scales through the use of satellite systems [18][19][20][21][22]. Concerning condition (i), the remarkable fact was shown in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…[7,9], it was shown that two-photon multidimensional OAM-entangled states generated by means of SPDC can be effectively distilled into states very close to | Z αβ , thus making the contributions coming from states having higher OAM negligible. 1 This effectively makes the Hilbert space spanned by photonic OAM states isomorphic to that of a spin-1 particle, or qutrit, so that | Z αβ describes a maximally entangled two-qutrit state. The initial state is thus taken to be | (0) ABαβ = |N A 0 ,N B 0 AB | Z αβ , whose dynamics under Eqs.…”
Section: B Entanglement Transfer Processmentioning
confidence: 99%
“…The rich variety of coherently exploitable degrees of freedom with which a photonic system is endowed has been extensively used in recent years in order to demonstrate the building blocks of quantum technology protocols, including quantum cryptography [1], quantum repeaters [2], teleportation, and quantum computing [3]. In this context, the exploitation of orbital angular momentum (OAM) carried by light is settling as a new and exciting opportunity for coherent manipulation at the classical and quantum levels [4].…”
Section: Introductionmentioning
confidence: 99%
“…[9,10], and references therein). Currently, there is much interest in testing quantum mechanics for large space distances and eventually in implementing quantum information protocols in global scales [11][12][13][14][15]. Photons seem to be the ideal physical objects for this purpose.…”
mentioning
confidence: 99%